A novel lifetime prediction for integrated LED lamps by electronic-thermal simulation. (July 2017) - Sun, Bo; Fan, Xuejun; Ye, Huaiyu; Fan, Jiajie; Qian, Cheng; van Driel, Williem; Zhang, Guoqi
Abstract: In this paper, an integrated LED lamp with an electrolytic capacitor-free driver is considered to study the coupling effects of both LED and driver's degradations on lamp's lifetime. An electrolytic capacitor-less buck-boost driver is used. The physics of failure (PoF) based electronic thermal simulation is carried out to simulate the lamp's lifetime in three different scenarios: Scenario 1 considers LED degradation only, Scenario 2 considers the driver degradation only, and Scenario 3 considers both degradations from LED and driver simultaneously. When these two degradations are both considered, the lamp's lifetime is reduced by about 22% compared to the initial target of 25, 000 h. The results of Scenario 1 and 3 are close to each other. Scenario 2 gives erroneous results in terms of luminous flux as the LED's degradation over time is not taken into consideration. This implies that LED's degradation must be taken into considerations when LED and driver's lifetimes are comparable. Highlights: The coupling effect of both LED and driver's degradations on an integrated LED lamp's lifetime is investigated. The electronic-thermal simulation, a physics of failure (PoF) based methodology, is used in the present study. An electrolytic capacitor-less LED driver is considered in this paper.